Investigating the use of defect-containing timber from young Eucalyptus plantations for manufacturing engineered products - Balboni, Bruno Monteiro (2022)
The increasing demand for timber globally has led to a search for sustainable wood sources. Young Eucalyptus plantations are a potential source of timber, taking advantage of their fast growth and high adaptability to a wide range of climatic conditions. Young trees usually contain undesirable features, such as knots, warping, and high contents of juvenile wood, apart from providing timber of limited cross-sectional dimensions, what can be overcome by the manufacture of engineered products. We aimed to address some key points, from the wood quality and mechanical properties point of view, for the adoption of short-rotation Eucalyptus plantations to manufacture engineered wood products. Among the high-productive clones already in use in the Brazilian bioenergy industry, we have identified some with desirable wood mechanical properties even at early ages (seven years-old). We developed and tested a bow and spring index in young and mature E. grandis timber boards which allows us to identify and segregate timber portions whose localized distortion is too high, helping to use the low warping sections to compose finger-jointed lamellas for engineered wood products. When testing the adhesion strength on knot-containing timber from young E. grandis in relation to clear wood, we found that knots reduce wood adhesion strength only when density is above 0.65 g cm-3, reinforcing the benefits of stratifying lamellas on glued laminated beams. High-density lamellas are positioned on zones with higher compression and tensile stress demand, but where shear stress is low. This fact, together with the low proportion of knots on lamellas\' surfaces, makes the influence of knots on the adhesion of wood of young Eucalyptus less significant. We build an tested glued laminated beams using timber from young E. grandis with different levels of bow, adding presstress to the beams. Prestress did not influence the beams\' load capacity as hypothesized. However, laminated beams returned mechanical properties adequate for structural applications, even though 80% of lamellas did not meet the minimum requirements of national timber standards. While knots in the compression zone did not influence the beams\' behavior, knots on the tension side were the points where rupture started. However, only one beam had the bending behavior and strength affected by the knot, although not enough to affect the average and the variation of the data. In turn, knots did not influence beams\' bending stiffness independently of their position. The results showed young Eucalyptus timber has a high potential for manufacturing engineered products, especially in countries where Eucalyptus is already well established as a forest culture, such as Brazil, South Africa, and Chile. There are several benefits of using this timber source, from the fast-growing raw material production and processing, lower risks, and earlier payout, to the possibility of establishing plantations close to the consumer market. There is, however, the need for assessing the yield of each processing step and the economic viability of manufacturing engineered wood products from young Eucalyptus forests.